Laporan Kasus : Feline Immunodeficiency Virus pada Kucing Moi di Surabaya - Kurnianto, Ady; Millenia, Maria (JURNAL KAJIAN VETERINER, 2023)
Feline immunodeficiency (FIV) is a disease caused by retroviridae of the lentivirus genus and is dangerous for cats. This virus attacks the cat's immune system. FIV disease can be transmitted horizontally via as saliva and body fluids. 5-month-old black and white Persian cat named Moi, brought by the owner with complaints of vomiting yesterday, refusing to eat and drink, soft stool, no coughing and sneezing, weakness. On physical examination showed a temperature of 40.1 °C with a body weight of 1.5 kg, clinical symptoms were found in the form of gingivitis, canker sores, conjunctivitis, pale pink mucous membranes, fever, flu symptoms from the nose with clear discharge, crepitus in both ears. Diagnosis of Moi Cats based on anamnesis, physical examination, clinical symptoms, and supporting examinations is diagnosed with Feline immunodeficiency virus (FIV). Case are treated using a combination of antibiotics, anti-inflammatories, fluid therapy, antiemetics, gastrointestinal linings, immune boosters, blood boosters, and cardiac pacemakers. After 4 days the cat Moi was declared dead due to failure of platelet hemostasis, bleeding, and heart failure.